GEOLOGIA DEL QUATERNARIO E GEOMORFOLOGIA DELLA BASSA VALCHIAVENNA (SO) - D. Tantardini (Università degli Studi di Milano, 2016)
Situated in the Central Alps, Valchiavenna (Chiavenna Valley) has been geologically studied for centuries. From 2009, with a new field survey of the Upper Valchiavenna (an area of 194 square km), the Department of Earth Sciences of the University of Milan has started a methodical study of the Quaternary geology and of the geomorphology of the valley, which were poorly known, with the aim to obtain homogeneous, complete and detailed data. Given the geological and geomophological complexity of the area, in this study the field survey was carried out by a single person. This granted a privilege to the quality of the field survey, and permitted to obtain homogeneous field data. Both the Quaternary deposits (identified on the basis of the genetic sedimentary process) and the morphologies (of any origin: structural/tectonic, from slope dynamics, from erosion or deposition in glacigenic or fluvial environment, from periglacial processes) have been surveyed. This work continues in the Lower Valchiavenna (384 square km) the previous study, completing the field survey for the entire valley and concentrates on mapping and on the description of the field survey results for the Lower valchiavenna area. The map of geomorphology and Quaternary deposits of Lower Valchiavenna has been drawn at a 1:15.000 scale using a Geographic Information System from 1: 10.000 field data and subdivided into four thematic maps, concerning structural morphologies, slope dynamics, fluvial and glacial morphologies, periglacial morphologies. The identification of minor brittle faults and the measure of orientation data permitted to identify different structural patterns in the different tectonic units. Data show a strong connection between minor brittle faults and the valley network. Slope instability phenomena such as landslides or rock falls or deep-seated gravitational slope deformations (DSGSD) have been identified; and also the areas where the rock poor geomechanical characteristics. Permafrost presence at high altitudes was verified by the ...